Model-checking temporal properties of real-time HTL programs - Carvalho, André Ribeiro de (2010)
This paper describes a tool-supported method for the formal verification of timed properties of HTL programs, supported by the automated translation tool HTL2XTA, which extracts from a HTL program (i) an Uppaal model and (ii) a set of properties that state the compliance of the model with certain automatically inferred temporal constraints. These can be manually extended with other temporal properties provided by the user. The paper introduces the details of the proposed mechanisms as well as the results of our experimental validation.